Pharmacological Effects and Molecular Protective Mechanisms of Astragalus Polysaccharides on Nonalcoholic Fatty Liver Disease - Zhang, Jing; Feng, Quansheng (Frontiers in Pharmacology, 2022)
Nonalcoholic fatty liver disease (NAFLD) has been renamed metabolic dysfunction-associated fatty liver disease (MAFLD), a condition for which there is now no authorized treatment. The search for new medications to treat MAFLD made from natural substances is gaining traction. The function of anti-oxidant, anti-inflammation, hypoglycaemic, antiviral, hypolipidemic, and immunomodulatory actions of Astragalus polysaccharides (APS), a chemical molecule isolated from Astragalus membranaceus, has become the focus of therapeutic attention. We have a large number of papers on the pharmacological effects of APS on NAFLD that have never been systematically reviewed before. According to our findings, APS may help to slow the progression of non-alcoholic fatty liver disease (NAFL) to non-alcoholic steatohepatitis (NASH). Lipid metabolism, insulin resistance (IR), oxidative stress (OS), endoplasmic reticulum stress (ERS), inflammation, fibrosis, autophagy, and apoptosis are some of the pathogenic pathways involved. SIRT1/PPARα/FGF21, PI3K/AKT/IRS-1, AMPK/ACC, mTOR/4EBP-1/S6K1, GRP78/IRE-1/JNK, AMPK/PGC-1/NRF1, TLR4/MyD88/NF-κB, and TGF-β/Smad pathways were the most common molecular protective mechanisms. All of the information presented in this review suggests that APS is a natural medication with a lot of promise for NAFLD, but more study, bioavailability studies, medicine type and dosage, and clinical proof are needed. This review could be useful for basic research, pharmacological development, and therapeutic applications of APS in the management of MAFLD.